2018
DOI: 10.1021/acssuschemeng.8b03726
|View full text |Cite
|
Sign up to set email alerts
|

A Process for Well-Defined Polymer Synthesis through Textile Dyeing Inspired Catalyst Immobilization

Abstract: Industrialized textile dyeing technology has inspired a scalable and low-cost process for immobilization of a photoredox catalyst onto commercial cotton threads to prepare unique heterogeneous catalyst composites; these composites are capable of regulating photoinduced controlled/"living" radical polymerization in batch and flow reactors. Freebase porphyrin (e.g., tetraphenylporphyrin (TPP)), an efficient photocatalyst for photoinduced electron/energy transfer−reversible addition−fragmentation chain transfer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 83 publications
1
41
0
1
Order By: Relevance
“…Figure A showed a linear plot of ln([ M ] 0 /[ M ] t ) against light irradiation time, indicating the propagating radical concentration is constant throughout the reaction time. An induction period (∼3.5 h) was observed in the polymerization, which was induced by the oxygen in the cotton thread that cannot be eliminated completely by degassing, as reported in the previous work . The linear increase of M n versus monomer conversion, as well as the low PDIs (<1.10) further revealed that this polymerization process was well‐controlled (Figure B).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Figure A showed a linear plot of ln([ M ] 0 /[ M ] t ) against light irradiation time, indicating the propagating radical concentration is constant throughout the reaction time. An induction period (∼3.5 h) was observed in the polymerization, which was induced by the oxygen in the cotton thread that cannot be eliminated completely by degassing, as reported in the previous work . The linear increase of M n versus monomer conversion, as well as the low PDIs (<1.10) further revealed that this polymerization process was well‐controlled (Figure B).…”
Section: Resultssupporting
confidence: 74%
“…The hydroxyl groups on C6 (the secondary carbon) of the glucose units in cellulose provides excellent catalyst anchoring sites with low steric hindrance . In our previous work, high loading of functionalized porphyrins (carboxylic acid and triazine functionalities) was accomplished by using natural cotton, cotton sponge, and cotton thread as supporting materials without prior surface modification . In this work, given the inherent carboxylic acid group in EY molecule, a simple yet effective carbodiimide coupling reaction between EY and cellulose materials presents a straightforward approach for EY immobilization onto cotton thread (Scheme A).…”
Section: Introductionmentioning
confidence: 99%
“…1b) was performed by modifying previously reported procedures. 85,86 The rst step in the synthesis to generate the monohydroxyl free-base tetraphenylporphyrin (TPP-OH) was the most costly in terms of yield (i.e., $5%) given that the reaction produces a statistical mixture of mono-, bis-, tris-, and tetra-functionalized TPP. However, isolation of the desired product (TPP-OH) was readily achieved using standard silica gel chromatography using a gradient mobile phase of hexane : CH Fig.…”
Section: Synthesis and Characterization Of The Viologen-based Crosslimentioning
confidence: 99%
“…We used non‐woven fabric as the substrate, as it was necessary to synthesize the polymers in our laboratory, and it is easier to form the radicals evenly across a non‐woven substrate with the equipment that was available. Robust, inexpensive fibrous materials are chosen because they are available in many variations [39–40] . Initially, polyethylene non‐woven fabric was irradiated with an electron beam to form radicals, then the irradiated fabric was dipped into monomer solution and heated under N 2 .…”
Section: Figurementioning
confidence: 99%